Welding Technique Training and Neon Box Advertising Board for Youth Work Groups in Areas Affected by Earthquake Disasters - Arwizet Karudin; Ambiyar Ambiyar; Bulkia Rahim; Remon Lapisa (Jurnal Aplikasi IPTEK Indonesia, 2019)
Abstract: Cubadak Air and Sikapak Barat villages are two villages from many villages affected by the earthquake that hit West Sumatra in 2009. The impact is still felt today. More than eighty percent of the houses and economic facilities of the people in this area were destroyed, so there was a lot of unemployment in this village. The purpose of this activity was to train groups of out of school youth in Cubadak Air and Sikapak Barat villages about welding techniques and the manufacture of neon box advertising boards. The method used in this activity is the provision of theories about the science of materials, welding, workshop management, welding practice techniques, and the manufacture of billboards. The results of this activity were the completion of the signboard of the Al-Abrar Great Mosque and the "Piaman Saiyo" Community Training Center in Cubadak Air Village.Key words: Workmanship, Billboards, Neon boxes, Skills Abstrak. Desa Cubadak Air dan Sikapak Barat adalah dua desa dari banyak desa yang terkena bencana gempa yang melanda Sumatera Barat pada tahun 2009 lalu. Dampaknya hingga kini masih terasa. Lebih delapan puluh persen rumah dan fasilitas perekonomian masyarakat di daerah ini hancur, sehingga di desa ini banyak terjadi pengangguran. Tujuan dari kegiatan ini untuk melatih kelompok pemuda putus sekolah di Desa Cubadak Air dan Sikapak Barat tentang teknik pengelasan dan pembuatan papan iklan dari neon box. Metode yang dilakukan dalam kegiatan ini adalah pemberian teori tentang ilmu bahan, las, manjemen bengkel, teknik praktek las, dan pembuatan papan iklan. Hasil yang dicapai dari kegiatan ini adalah telah selesainya papan nama Masjid Raya Al-Abrar dan Pusat Pelatihan Masyarakat “Piaman Saiyo” di Desa Cubadak Air.Keywords: Tuna karya, Papan iklan, Neon box, Skill